2002
DOI: 10.1086/341786
|View full text |Cite
|
Sign up to set email alerts
|

The Radio Properties of Composite LINER/H ii Galaxies

Abstract: Arcsecond-resolution VLA observations-newly obtained as well as published-of 40 nearby galaxies are discussed, completing a study of the radio properties of a magnitude-limited sample of nearby galaxies of the composite LINER/H ii type. Our results reveal an overall detection rate of at least 25% active galactic nucleus (AGN) candidates among these composite sources. The general properties of these AGN candidates, as compared to non-AGN composite sources and H ii galaxies, are discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 56 publications
(149 reference statements)
1
10
0
Order By: Relevance
“…LINER 2s have a lower detection rate than LINER 1s (38% versus 63%; see Table 1), but the same pattern is reflected almost exactly within the Seyfert population (detection rate 30% for type 2s versus 72% for type 1s). Transition objects, on the other hand, clearly differ, showing a markedly lower detection rate of only 16%, consistent with the 8.4 GHz survey of Filho, Barthel & Ho (2000, 2002a, 2006, where the detection rate is ∼ 25%. The statistical differences in the Hubble type distributions of the three AGN classes slightly complicate the interpretation of these results.…”
Section: Radio Coressupporting
confidence: 82%
See 4 more Smart Citations
“…LINER 2s have a lower detection rate than LINER 1s (38% versus 63%; see Table 1), but the same pattern is reflected almost exactly within the Seyfert population (detection rate 30% for type 2s versus 72% for type 1s). Transition objects, on the other hand, clearly differ, showing a markedly lower detection rate of only 16%, consistent with the 8.4 GHz survey of Filho, Barthel & Ho (2000, 2002a, 2006, where the detection rate is ∼ 25%. The statistical differences in the Hubble type distributions of the three AGN classes slightly complicate the interpretation of these results.…”
Section: Radio Coressupporting
confidence: 82%
“…To a sensitivity limit of P rad ≈ 10 18 − 10 20 W Hz −1 at 5 GHz, and a resolution of ∆θ = 1 ′′ , they found that none of the galaxies contains a compact radio core. The VLA study of Filho, Barthel & Ho (2000) also failed to detect radio cores in a more heterogeneous sample of 12 H II nuclei.…”
Section: Robustness and Completenessmentioning
confidence: 94%
See 3 more Smart Citations